2014
DOI: 10.1371/journal.pone.0106469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Breast Examination As the Recommended Breast Cancer Screening Modality in a Rural Community in Malaysia; What Are the Factors That Could Enhance Its Uptake?

Abstract: Breast cancer is the most common cause of deaths and the most frequently diagnosed cancer among women worldwide. This study aimed to determine the prevalence of breast cancer screening, specifically on clinical breast examination, and the predictors of its uptake among women in Malaysia. A cross-sectional study was carried out in five selected districts whereby women aged between 20 to 64 years old, from a total of 1000 households were interviewed. A total of 1192 women responded to the survey of which 53.3% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 11 publications
(11 reference statements)
3
33
1
Order By: Relevance
“…Even so, knowledge alone may not be sufficient to prompt the correct action. In addition, it was shown that women in rural areas had lower awareness and knowledge compared to urban women (Farid et al, 2014). This may be due to limited access to health education and inability to receive BSE, CBE or mammogram due to transport or inaccessibility of tests (Farid et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even so, knowledge alone may not be sufficient to prompt the correct action. In addition, it was shown that women in rural areas had lower awareness and knowledge compared to urban women (Farid et al, 2014). This may be due to limited access to health education and inability to receive BSE, CBE or mammogram due to transport or inaccessibility of tests (Farid et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, rural women were shown to have less awareness compared to those living in urban areas (Kanaga et al, 2011). In terms of knowledge, women in rural areas had an average to poor score (Farid et al, 2014). Comparing the East Coast and West Coast of Malaysia, it was revealed that women in Pahang (East Coast) had highest awareness as compared to Perak (West Coast) (Norlaili et al, 2013).…”
Section: Knowledge Of Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations